POWTOON FOR TEACHING ENGLISH IN THE SECOND GRADE - Hari, Ketut Wirama (Universitas Pendidikan Ganesha, 2019)
Nowadays elementary school students need learning media to help them learn more effectively. Therefore, this research aimed at implementing and evaluating PowToon as developed media for teaching English in the second grade. The present research employed descriptive qualitative method. There are 6 types of videos used during implementation, namely (1) Fruits, (2) School Uniform, (3) Birthday Party, (4) Parts of Face, (5) Pets, and (6) Parts of the Tree. The instruments were an interview guide and a questionnaire that were used to determine the teacher’s and students’ responses in the evaluation. It was found that PowToon could be used to teach the second graders English. The questionnaire showed that the animation video could attract the students' attention and motivate them. In addition, the results of teacher’s interview showed that this media could assist the teachers in teaching. Therefore, it is recommended for teachers to use PowToon video animation when teaching.